Learning social entrepreneurship: Experiences of sociology students - Basharat Hussain; Abdullah Zafar Sheikh; Tehniyat Fatima (Cogent Business & Management, 2022)
Social entrepreneurship paves the way for both social and economic development of a country. To learn this unique combination, social entrepreneurship education plays a vital role. It positively influences the entrepreneurial intentions of the students. Previously this education was limited to the realm of business studies, but more recently social entrepreneurship education is encompassing students from different disciplinary backgrounds. The present study aims to highlight the learning experiences of the Sociology students during Social Entrepreneurship. Thematic analysis of the textual reflective papers was conducted to highlight different aspects of their learning experiences. The students were motivated to study the course majorly because of their experience with the instructor. Financial motivations were a main driver towards the selection of the course because social entrepreneurship was viewed as a lucrative alternative owing to the rising unemployment in the country. The students highlighted that experiential learning is indispensable to social entrepreneurship education which was severely affected due to the Covid-19 pandemic as the transition towards online education took place. Gender played a significant role in the motivation and inspiration gained from the course as most female students perceived social entrepreneurship education to be a path towards financial independence. Social entrepreneurship education is a growing filed in Pakistan and the higher educational institutes must take into account the learning experiences of students with different disciplinary backgrounds to enhance the overall entrepreneurial capacity of students by overcoming the barriers that they face. The current study presents insights for the growth of social entrepreneurship education in Pakistan.
Keywords: 650; higher education; Pakistan; Social entrepreneurship education; sociology students